Efficacy of ecological compensation programs under centralized management: evidence from China - Xie, Xiaoyao; Tao, Wentai; Wang, Yuhong (Frontiers in Marine Science, 2025)
Watershed ecological compensation programs have emerged as a pivotal instrument for internalizing the externalities associated with watershed ecological protection. In most countries, the direct participants in ecological compensation projects are ordinary persons and enterprises, but in China, the direct participants are local governments and the central government, which to some extent affected the efficacy of the compensation programs. This study used PSM–DID to analyze the efficacy of the Xin’an River Basin Ecological Compensation Project (Xin’an-BECP) and calculated the loss of opportunity developed in the upstream area through EKC (Environmental Kuznets Curve) fitting, which makes the benefit assessment of government-led ecological compensation projects more objective and provides a model that can be used to analyze the benefits of BECP in developing countries. Our results show that (1) the treatment effect of the Xin’an-BECP is not obvious; (2) the compensation funds gained by the upstream area are much lower than the theoretical opportunity loss; and (3) enterprises are not transaction participants in the Xin’an-BECP. Finally, based on the conclusions of the discussion, we propose specific policy recommendations to guide developing countries in increasing the compensatory effects of BECP in the context of growing demand for economic development.